Validación de un cuestionario de satisfacción de pacientes con el servicio de dispensación en farmacias comunitarias() - Armando Carle, Pedro D. (Aten Primaria, 2007)
OBJECTIVE: To analyze the validity and reliability of a patient satisfaction questionnaire about drug dispensing in Argentine community pharmacies. DESIGN: Descriptive, cross-sectional study. SETTING: Community pharmacies of Argentina that voluntarily agreed to take part in the study. PARTICIPANTS: All patients or their careers who attended the pharmacies during the period of the study (March and April, 2006) and knew how to read and write. MAIN MEASUREMENTS: Scores on the satisfaction scale of the questionnaire. RESULTS: Twenty-seven pharmacies from 6 provinces of Argentina took part; 473 questionnaires were obtained with a 72.4% response rate. Factorial analysis revealed one single component that explained 54.8% of total variance. A 0.90 Cronbach's alpha coefficient was obtained and Pearson's correlation between each of the items and the total score on the scale showed that all items correlated with each other (P<.01). Patients expressed additional comments in 124 questionnaires (26.2%). These concerned the quality of care received and other aspects, such as gratitude, cost of medicines, insufficient stock, and friendliness. CONCLUSIONS: The questionnaire, in showing evidence of content validity, validity as internal structure, validity related to other variables, and reliability, could assess patient satisfaction with the drug dispensing service in the community pharmacies of Argentina.